Vibrational World - Thomagjini, Albert (JOURNAL OF ADVANCES IN PHYSICS, 2017)
Thinking that time and mass are correlated, like mass and energy are ( E = m*c^2 ). The period of oscillation of the simple oscillator, with a mass M and spring with coefficient k, is given by: T = 2*Pi*Sqrt(M/k); (1) or T Sqrt(M); (2)